Quinze anos de ação comunitária: uma análise descritiva de uma prática educacional - Vlasman, Petrus Maria (1977)
This studv examines the Community Action in noor areas, durinq the 1950' s un to 1975. In fact, i t tries to evaluate this modality of educational intervention on the basis of the cateqory of dependence-ind enendance. It a ssu~es that community action, by definition, should qenerate in the tarcret Donulations a nosture of independance in order to create inter-denendence for the attain ment of the aims of Develonment. The main object of the study is the historical evolution of FASE, of nrivate organisation of community action, vis a vis other public and private organisations, that work in the so called marginal communi ties. ST)ecif ically, i t describes and ana lyses the definition and redefinitions of obiectives of community action ano the reformulations of pedaqogical strateaies, and arrives at the conclusion that three hasic types of intervention have been used : 1. Assistencialism, givinq to the poor what they need , therefore increasinq the denennence of the carnrumity in relation to the interveninq institution i 2. Comnuni tv Develo}''>ment (CD), follovlÍna recomendations of the UN in the 1960' s , increases in the narticina tion of the communities in the definition and imnle mentation of its own development ; 3. Education for develonrnent, adooeted 1970 : s and , initially, limiteo to a in the earlv simnle imnrove ment of the human capital and, later on, with the chanqe in the Braz ilian political structure, redefined as a nedaaoqy of 'conqcientization' and participation. The ' first t ype did not reauire or involve anv soecif.ic methodoloqy. The seconrl made extensive use of. nlanninq techni0ue and psycho-social theories. The study concludes that the Brazilian experience with CD, as a whole, was not succesfull, because of political and socio-econornic factors, lack of ~loba l planninq and superficiality in the conduct of the process, rather than lack of continuity. 50, CD becarne restrict to orqanisation of oommunity, to the exnansion and i mprovernent of some basic problems of fisical infrastructure and never was able to attack the socio-economic structural oroblems that causes marginalisation and denenden ce . The third t y~ ~ combined socioloqical, political ano educacio nal methodologies, trying , in the first moment, to reàuce the individuals in relation and within CaoitalisM, and, in the second moment, to consider and attack the structural socio-economic nro blems of the country in a stage of dependent capitalismo As a general conclusion, it is advanced that the Community Action essentially, depends on the political situation and on the socio-economic structures to lneet its rnain o b iective, that is the independance of the individuals and communities in a marqinal condition and the transformation in equal partners and participants in the process of national development.